Recent acquisitions on oxyprenylated secondary metabolites as anti-inflammatory agents - Fiorito, Serena; Epifano, Francesco; Taddeo, Vito Alessandro; Genovese, Salvatore (European journal of medicinal chemistry, 2018)
Oxyprenylated secondary metabolites from plants, fungi, and bacteria, and their semisynthetic derivatives have been subject of growing interest during the last decade. Such natural products in fact have been discovered as potentially novel lead compounds for a series of pharmacological activities, mainly in terms of anti-cancer and anti-inflammatory ones. Especially during the last 5 years, a wider panel of prenyloxy secondary metabolites have been investigated from chemical and biological points of view and these include benzoic acids, alcohols, aldehydes, chalcones, anthraquinones, 1,4-naphthoquinones, other than the well known oxyprenylated ferulic acid and coumarin derivatives. The aim of this comprehensive review is to focus on the anti-inflammatory properties and related mechanisms of action of selected classes of oxyprenylated naturally occurring compounds and their semisynthetic analogues covering the literature period from 2011 to 2017. In vitro and in vivo data on their pharmacological activity triggering different pathways of the overall inflammatory machinery as well as structure activity relationship acquisitions will be summarized in order to make a detailed survey of the most recent reports on the potential of the title compounds as a novel class of anti-inflammatory agents. [Display omitted] •This review descrìbes the most recent acquisition on oxyprenylated compounds as anti-inflammatory agents.•This review describes the chemical structures of the most active oxyprenylated derivatives.•Structure-activity relationship data of title natural products will be presented.•The review will contribute for planning new research on oxyprenylated secondary metabolites.